ОСОБЛИВОСТІ ПРОЦЕСУ ФОРМУВАННЯ ІНФОРМАТИЧНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ПЕДАГОГІВ ПРОФЕСІЙНОГО НАВЧАННЯ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2022)
At time of digital society the problem of the concept ‘informative competence’ is of greatimportance. It can be raised in both the sphere of everyday life of modern man and the field of would-bespecialists’ professional training. In the area of the latter the informative competence formation of wouldbe professional education teachers is to be significantly concerned, thus the specific tasks to beaccomplished by them are connected with the use of modern technologies and information processing.The purpose of the article deals with defining of number of specific features of informative competenceformation of would-be professional education teachers while realizing professional and educationalprogram 015 Professional Education. That may promote the optimizing of the appropriate educationalprocess.I order to describe the state and level of the studied problem development, conclusions andrecommendations formation the method of analysis and synthesis was used.The work outlines the basic concept of informative competence on the basis of the study results of nativeand foreign scientists. Thus, informative competence is described as integrative dynamic personalcharacteristic. It includes complex of valuative and motivated orientations and reflexive activity,mastering the skills to work with information (analysis, transformation, search and others) andinformation technologies, as well as special knowledge and abilities that are necessary for substantial andjustified choice, their optimal use while solving professional and educational studying tasks at the time oftotal digitalization and demands of digital society.Having analyzed the standard ‘Teacher of professional education’ and the standard of higher education ofUkraine, of the first Bachelor level, of the specialty 015 Professional Education, a number of specificfeatures of informative competence formation of would-be professional education teachers is presented.That is proved by determining of the content of educational components in the field of the followingprofessional education teacher’s labour functions: planning educational process, producing educationalprocess, performing self-studying activity, producing methodological work, accomplishing research andexperimental work, performing monitoring of educational activity, holding professionally oriented work.